Risk Management and Shareholders’ Wealth Maximization - Ogundajo, Grace O; Adefisoye, Adekunle; Nwaobia, Appolos N (International Journal of Business, Economics and Management, 2020)
Risks are fundamentally part of business operational models; it cannot be completely eliminated and if not efficiently managed could result to loss of value. Wealth creation could only take place when the prevailing financial risks in the banking sectors are identified and carefully handled. An expost-facto study of 100 firm-year observations was conducted using ten listed Deposit Money banks in Nigeria for a period of 10 years from 2009 to 2018. The results of the multiple regression analysis carried out revealed that risk management significantly affected shareholders’ wealth of listed banks. Credit risk (NPLR) and operating efficiency risk (OPER) had significant negative effect on Market Value (MV) while capital risk and liquidity ratio (LQR) had significant positive effect on market value (MV). This study concluded that four elements of risk (credit risk, capital risk, operating risk, liquidity risk) significantly affected shareholders’ wealth of listed banks in Nigeria. Therefore, the management of the Nigerian banks should ensure that non-performing loan ratio to total loan is kept at its minimum; ensure adequate liquid fund in meeting customers demand as when needed, engage competent hands where deemed necessary in their operations to mitigate operating efficiency risk and possess adequate capital ratio in accordance with CBN minimum capitalization ratio, if possible, beyond the minimum required by the regulatory bodies.